Inhibitory Test of Garlic Extract (Allium sativum L.) against the Growth of Staphylococcus aureus Bacteria, and Review According to the Islamic Religion - Dinda Mulya Arrifa; Pratami Adityaningsari; Firman Arifandi (Junior Medical Journal, 2022)
Skin infection is one of the most common diseases in Indonesia. The most common skin and soft tissue infections caused by pyogenic bacteria are S. aureus and group A hemolytic Streptococcus, including S. pyogenes (Perdoski, 2017). One of the bacteria that often causes skin infections is Staphylococcus aureus. One of the plants that has long been believed to have good antibacterial activity against bacteria is garlic (Allium sativum) (Duman, 2008). This study used Kirby Bauer diffusion using NA and MHA media. Garlic extract has various concentrations of 20%, 25% and 30% with clindamycin as a positive control and distilled water as a negative control. The results of this study stated that no inhibition zone was formed, which was indicated by the absence of antibacterial activity in garlic extract on Staphylococcus aureus bacteria. The conclusion is that garlic extract extracted with 99% methanol does not have the effectiveness of inhibiting the growth of Staphylococcus aureus bacteria.